The Sultan, Parti Rakyat Brunei, and International Interest In North Kalimantan Affair 1962-1963 - Adriani, Nour Muhammad (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2019)
Brunei Revolution in 1962 despite of its small scale is an important event which lead to an international conflict occurred in the region in years next. As its international historical context, the issue about who is the most responsible for triggering it remain in debate. The Sultan of Brunei is one of untouchable party who can be also viewed from this perspective. His reluctance and unresponsive attitude; decision to seize the people's democracy; and arrogance in Malaysia's case, left all interested parties gaining momentum to pressure him to decide. The Brunei People Party (PRB) became one of the parties who tried to do it, with its often-neglected aspirations for national independence, supported by the people, sympathetic neighbours, and left-leaning nations at the time. This failed rebellion also resemble a symbol of relatively untouchable people of monarch which absent from historical critics regarding its powerful position in the modern politics.